Radiation effects on oscillating vertical plate with uniform heat and mass flux - Chandrakala, P.; Narayana Bhaskar, P. (Zielona Góra: Uniwersytet Zielonogórski)
Thermal radiation effects on flow past an impulsively started infinite vertical oscillating plate with uniform heat and mass flux is studied. The fluid considered here is a gray, absorbing-emitting radiation but a non-scattering medium. The dimensionless governing equations are solved using the Laplace-transform technique. The velocity, temperature and concentration are studied for different physical parameters such as the radiation parameter, phase angle, Schmidt number and time. The variation of the skin-friction for different values of the parameters is also shown in a table.
Keywords: oscillating vertical plate; radiation; heat flux; mass flux